2004
DOI: 10.1210/en.2004-0440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medroxyprogesterone and Estradiol on the Recovery of Spermatogenesis in Irradiated Rats

Abstract: Suppression of intratesticular testosterone (ITT) levels is required for spermatogenic recovery in rats after irradiation, but maintenance of peripheral testosterone (T) levels is important for many male functions. Considering the preservation of peripheral T while suppressing ITT, we tested the effects of a combination of a progestin, medroxyprogesterone acetate (MPA), plus T on spermatogenic recovery after irradiation, and compared its effects to those of T alone or T combined with estradiol (E2). Rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…However, lack of E 2 or estrogen receptor activity is associated with infertility (17,18), and injection of lactate in cryptorchid testes of adult rats significantly augments sperm production (39), lending support to the notion that lactate and E 2 are essential for spermatogenesis. In a recent study, E 2 has been demonstrated to induce Gc differentiation in 88% of seminiferous tubules of irradiated rats (40).…”
Section: Discussionmentioning
confidence: 91%
“…However, lack of E 2 or estrogen receptor activity is associated with infertility (17,18), and injection of lactate in cryptorchid testes of adult rats significantly augments sperm production (39), lending support to the notion that lactate and E 2 are essential for spermatogenesis. In a recent study, E 2 has been demonstrated to induce Gc differentiation in 88% of seminiferous tubules of irradiated rats (40).…”
Section: Discussionmentioning
confidence: 91%
“…Ischemia was induced by a clockwise 720°torsion applied to the spermatic cord by open surgery (21) for 1 h, followed by a return to the natural position to allow for reperfusion of the tissue. Exposure of testes to ionizing radiation was performed according to published procedures and doses (22,23). Briefly, anesthetized animals were irradiated locally at a distance of 100 cm with a single total dose of 6.5 gray of X-rays produced by a linear accelerator.…”
Section: Methodsmentioning
confidence: 99%
“…During studies of regulation of spermatogenic recovery in rats after gonadotoxic therapy for cancer, we found that estrogen stimulated the recovery of spermatogonial differentiation [1][2][3], but the mechanism of action was not identified. Estrogens indeed have widespread effects on spermatogenesis and male reproduction, but those effects and the mechanisms involved are quite complex [4,5].…”
Section: Introductionmentioning
confidence: 98%